The positivist mirage: Legal interpretation and ideology in Republican Spain (1931-1936) - Pérez Trujillano, Rubén (Historia y Política, 2024)
This article addresses the influence of ideological and moral factors in judicial reasoning during the period 1931-1936, both in the Spanish Supreme Court and in lower courts of justice. The aim of the systematic analysis of judgments and judicial proceedings is to know how judicial decisions affected the definition of rights, powers and authority in a severe context of regime change. To this end, the normative and cultural background is studied. This starting point allows the article to frame judicial interpretation in a set of conditions and inertias established in the 19th century. On the other hand, the study of the structure of criminal judgements shows how the peculiar ideology of the judiciary actively conditioned the validity of the laws to the respect for certain extra-positive values and principles. In conclusion, different dimensions of the tension between judicial interpretation and the legal and constitutional regime of the Spanish Republic are highlighted.
Keywords: Constitution; judicial power; judicial interpretation; positivism; Second Spanish Republic